The Use of Edmodo in English Language Teaching for Senior High School in Surabaya - Hartono, Miki (New Language Dimensions, 2020)
Edmodo is one online learning platform that is accessible for teachers, students, and parents. This research aims to investigate the impact of using Edmodo among the students in Surabaya as well as their attitudes toward the use of Edmodo in the English classroom. This was action research on utilizing Edmodo in the English classrooms in one public senior high school in Surabaya. In addition, reflection among students was accommodated to determine students attitudes toward Edmodo in the classroom. The findings of this research show that using Edmodo leads to an improvement in students English skills. As part of reflection, students show positive attitudes toward the use of Edmodo in their class. Further studies should be conducted to investigate the further impact of Edmodo with diverse themes. In addition, some technical challenges of using Edmodo in the English classroom also need to be investigated in further studies.